Buildings including Northern Commercial Company building in Takotna on Takotna River, Alaska, September 1914 - University of Washington Libraries. Special Collections Division.
Dotted line drawn on photo to show route. Caption under photo: "Tacotna." Tacotna River. McPherson number: K482 PH Coll 495.2-51a Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.